(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
In the Epilogue to her latest book, Nancy Fraser highlights Covid 19 as ’a textbook example’ of the perils of global capitalism: ’the point where all cannibal capitalism’s contradictions converge’ (2022, p.160). As she sees it, this ’lethal binge’ has also produced profound consequences for care, turning ’already destabilised ... social reproduction into an acute care crunch’ (p.162).